노인의 사회적 요인(노인차별경험, 가족지지) 및 심리 정서적 요인(고독, 무력감)과 죽음불안 관계 - 김귀분(Kim, Kui Bun); 최연주(Choi, Youn Joo2) (Sŏngin Kanho Hakhoe chi, 2014)
Purpose: The aim of this study was to explore the factors contributing to death anxiety among elders through family support, ageism experience, loneliness and helplessness. Methods: The participants were 155 elders who lived in S city. The data were collected through a self-reported questionnaire in elders over age 65. In addition, their levels of death anxiety, family support, ageism experience, loneliness, helplessness and death anxiety were measured using a likert scale Data analysis using a t-test, one-way ANOVA, Pearson correlation and multiple regression analysis with the SPSS 20 program. Results: Significant differences were found in the levels of perceived death anxiety between the variables affecting death anxiety in elders. Pearson's Correlation were found family support (p<.001), ageism experience (p<.001), loneliness (p<.001) and helplessness (p<.001) with death anxiety. Conclusion: It is concluded that such variables should be considered for decreasing death anxiety by family support, ageism experience, loneliness and helplessness in elders.